(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Anastasia D. Melnik (Rostov-on-Don, Russian Federation) This article is devoted to the description of the fixed phrase scheme «Was + Pers. Pron1 [<Art1> Sub1] + <nicht> + Verb!(?)», functioning in the modern German language. The relevance of the study is due to the lack of study of this object space as well as its high importance for the practice of communication. The different scientific methods were used in the study. The fixed phrase scheme «Was + Pers. Pron1 [<Art1> Sub1] + <nicht> + Verb!(?)» is described in the structural, semantic, etymological, paradigmatic, syntagmatic, stylistic, phraseological and functional aspects. The article substantiates the phraseological status of this fixed phrase scheme and its belonging to the phraseological subsystem of the language. It is established that the scheme has two required components (changeable and unchangeable), is characterized by reproducibility, structural-semantic stability and integrity, idiomaticity and expressive, it has a fixed structure serving as a model to build similar sentences-statements. In General, the fixed phrase scheme «Was + Pers. Pron1 [<Art1> Sub1] + <nicht> + Verb!(?)» is enough frequency in the practice of speech communication due to its system and functional characteristics. Its use in conversation increases the efficiency of the communication process and gives it a relaxed character. Key words: syntactic phraseology; syntactic phraseological unit; fixed phrase scheme; German DOI 10.23683/1995-0640-2018-4-151-160